Implementasi Teknik Self Regulated Learning Hasil Belajar Pada Mata Pelajaran Fikih Siswa Kelas VIII Mts Al-Hidayah Air Hitam Gebang - Windi Aulia; Abdul Halim; Zaifatur Ridha (Jurnal Berbasis Sosial, 2022)
The learning outcomes of class VIII private MTs Al-Hidayah Gebang on the subject of fiqh on zakat material before applying self-regulated learning techniques have not been completed. This can be seen from the average score of the students' pretest results. The process of implementing fiqh learning in class VIII of Al-Hidayah Gebang Private MTs with the application of self-regulated learning learning methods in accordance with the plans that have been made, learning activities are carried out by no longer giving pretests to students, before starting learning the teacher motivates students to be more active than the previous meeting . The next step is still in the teacher's guidance in the form of class percentage actions and group work. The learning outcomes of class VIII MTs Al-Hidayah Gebang in the subject of fiqh material zakat, after the application of the self-regulated learning learning method in the first cycle the average value increased to 82 with the percentage of completeness of 82% and the percentage of completeness of learning had not reached 85%. And the second cycle the average value of students reached 87 (33 students) with a percentage of 100% completeness with an increase in the difference from cycle I to cycle II of 18%. with a 100% completeness percentage. Thus the second cycle experienced a significant increase, so the researchers concluded that there was no need to continue again in the next cycle. Thus, it can be concluded that it is proven that the self-regulated learning method is able to make students active and students are able to connect the material provided with real conditions in everyday life. This method also supports students in the learning process in class so that the learning outcomes achieved by students are better than before.